Measurements of plasma membrane potential changes in Saccharomyces cerevisiae cells reveal the importance of the Tok1 channel in membrane potential maintenance - Maresova, Lydie; Urbankova, Eva; Gaskova, Dana; Sychrova, Hana (FEMS yeast research, 2006)
K+ is one of the cations (besides protons) whose transport across the plasma membrane is believed to contribute to the maintenance of membrane potential. To ensure K+ transport, Saccharomyces cerevisiae cells possess several types of active and passive transporters mediating the K+ influx and efflux, respectively. A diS-C3(3) assay was used to compare the contributions of various potassium transporters to the membrane potential changes of S. cerevisiae cells in the exponential growth phase. Altogether, the contributions of six K+ transporters to the maintenance of a stable membrane potential were tested. As confirmed by the observed hyperpolarization of trk1 trk2 deletion strains, the diS-C3(3) assay is a suitable method for comparative studies of the membrane potential of yeast strains differing in the presence/absence of one or more cation transporters. We have shown that the presence of the Tok1 channel strongly influences membrane potential: deletion of the TOK1 gene results in significant plasma membrane depolarization, whereas strains overexpressing the TOK1 gene are hyperpolarized. We have also proved that plasma membrane potential is not the only parameter determining the hygromycin B sensitivity of yeast cells, and that the role of intracellular transporters in protecting against its toxic effects must also be considered.
Keywords: buněčná membrána; Saccharomyces cerevisiae; membránové potenciály; Potassium; Saccharomyces cerevisiae Proteins; Cell Membrane; Membrane Potentials; Saccharomyces cerevisiae - proteiny; Potassium Channels; draslík; draslíkové kanály; draslíko-vodíkové antiportéry; Potassium-Hydrogen Antiporters